2007
DOI: 10.1590/s0104-42302007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos pacientes portadores de lesão por pressão internados em hospital geral

Abstract: INTRODUÇÃOÚlceras por pressão são definidas pelo National Pressure Ulcer Advisory Panel (NPUAP) como "áreas localizadas de tecido necrótico que tendem a se desenvolver quando um tecido é comprimido entre uma proeminência óssea e uma superfície externa por tempo prolongado" 1 . Gradualmente, instala-se um processo isquêmico que resulta em uma lesão na pele, observada em quatro estádios de desenvolvimento, dependentes da manutenção dos fatores predisponentes ao seu surgimento 2 . Segundo o NPUAP, o método de cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
23

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 16 publications
0
9
1
23
Order By: Relevance
“…These patients' profiles were different from those in large part of other analyzed studies, which have applied the same assessment scales for pressure ulcer risk in countries like German, the Netherlands, Turkey and Brazil, where patients' profile include elderly female patients who were in bed and presented association of chronic degenerative diseases (12,(23)(24)(25) . The fact that our study was carried out at a specialized service of emergency care on traumatology and neurology, which is normally associated to traffic accidents involving young male individuals, has perhaps determined such difference.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These patients' profiles were different from those in large part of other analyzed studies, which have applied the same assessment scales for pressure ulcer risk in countries like German, the Netherlands, Turkey and Brazil, where patients' profile include elderly female patients who were in bed and presented association of chronic degenerative diseases (12,(23)(24)(25) . The fact that our study was carried out at a specialized service of emergency care on traumatology and neurology, which is normally associated to traffic accidents involving young male individuals, has perhaps determined such difference.…”
Section: Discussioncontrasting
confidence: 56%
“…And most of the studied population has developed PU, and 64% presented two injuries. In regards to detected PU incidence (59.5%) in Brazil, the problem's estimative at chronic care units was diversified, but some identified publications has shown a lower incidence in comparison to what was found during this research, like 5.9%; 39.7%; 26.8% and 11.8%, respectively (25)(26)(27)(28) . Thereby, it is urgent and necessary that preventive care attitudes can be performed; even in order to reverse other morbidities that have probably been caused by these injuries.…”
Section: Discussionmentioning
confidence: 63%
“…Estudos brasileiros realizados em UTIs de hospitais públicos obtiveram uma incidência variando de 19,2% a 41% (8,12) . Sousa et al (7) em estudo posterior a este, realizado na mesma instituição identificaram uma prevalência de 32,5% de UPP.…”
Section: Discussionunclassified
“…A study evaluating the risk of PU at home, identified a prevalence of 19.1% of PU and 70.2% of risk of injury in the individuals. Although these data only reflect the seriousness of the event in hospitalized patients, this information provides an understanding of the prevalence of PU in the home environment (2,(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%